Analysis of 5-hydroxytryptamine and its related indoles in cerebrospinal fluid of leukemic children by gas chromatography-mass spectrometry - Zhang Pingping; Wang Bo; Sun Yanmei; Gao Jian; Lian Kaoqi (Journal of Laboratory Medicine, 2020)
It is meaningful to quantify some neurotransmitters in cerebrospinal fluid (CSF) for pathology and clinical diagnosis. The objective of this study was to develop a rapid and reliable method for detecting 5-hydroxyindole ethanol (5-HTOL), 5-hydroxyindole acetic acid (5-HIAA), 5-hydroxytryptophan (5-HTP) and 5-hydroxytryptamine (5-HT) in CSF by gas chromatography-mass spectrometry (GC-MS), and explore the clinical significance of the levels of these neurotransmitters in CSF from acute lymphoblastic leukemia (ALL).